2020
DOI: 10.1186/s12893-020-00862-0
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation des-r-carboxy prothrombin for immunohistochemical assessment of vascular invasion by hepatocellular carcinoma

Abstract: Background We have previously shown the value of next-generation des-r-carboxy prothrombin (NX-DCP) for predicting vascular invasion in hepatocellular carcinoma (HCC). Since conventional DCP is inaccurate under some conditions, this study aimed to assess whether NX-DCP immunohistochemical staining was related to vascular invasion in HCC. Methods Fifty-six patients scheduled to undergo resection for single HCC were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…There is only limited understanding of the mechanisms for PVT. However, there are increased reports for some of the factors that may be involved, such as blood des-gammacarboxy prothrombin or inflammatory processes [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited understanding of the mechanisms for PVT. However, there are increased reports for some of the factors that may be involved, such as blood des-gammacarboxy prothrombin or inflammatory processes [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, despite PIVKA-II being a highly specific biomarker of HCC, it has not been widely accepted because its level is inaccurate in patients on warfarin or with poor nutritional status, such as alcoholic liver disease and jaundice, leading to vitamin K deficiency. [6] Unfortunately, most of the publications including the study by Lai and colleagues did not document standardized PIVKA-II measurement for detecting HCC; next-generation des-gammacarboxy prothrombin may prove to be a solution. [6] Besides PIVKA-II, there are many other biological markers that have been reported to be useful in predicting outcomes after LT, such as AFP-L3, [3] neutrophilto-lymphocyte ratio, [7] and lymphocyte-to-monocyte ratio.…”
Section: Protein Induced By Vitamin-k Absence Ii: Another Key To Crea...mentioning
confidence: 99%
“…[6] Unfortunately, most of the publications including the study by Lai and colleagues did not document standardized PIVKA-II measurement for detecting HCC; next-generation des-gammacarboxy prothrombin may prove to be a solution. [6] Besides PIVKA-II, there are many other biological markers that have been reported to be useful in predicting outcomes after LT, such as AFP-L3, [3] neutrophilto-lymphocyte ratio, [7] and lymphocyte-to-monocyte ratio. [8] In addition, 18 F-fluorodeoxyglucose-positron emission tomography avidity and response to locoregional therapy may also guide in ensuring acceptable tumor biology.…”
Section: Protein Induced By Vitamin-k Absence Ii: Another Key To Crea...mentioning
confidence: 99%
“…Secondly, NX-DCP ≥ 90 mAU/mL and the PIVKA-II/NX-DCP ratio ≥ 1.5 were associated with significantly larger tumor size and more frequent PV invasion. Studies by Kurokawa T et al [ 24 ] and Yamazaki S et al [ 25 ] also found that NX-DCP had a higher sensitivity for detecting vascular invasion (VI) in HCC than PIVKA-II and AFP. Sorafenib was the first targeted drug used in treating HCC, and a Japanese retrospective study evaluated for the first time the effect of sorafenib on serum NX-DCP in HCC patients.…”
Section: Pivka-ii and Its Specialized Variantmentioning
confidence: 99%